Development and experimental validation of a reduced-scale single-phase modular multilevel converter applied to a railway static converter - Rodrigues, Nuno (2023)
With special emphasis in recent years, an increase has been verified not only in demand but also in the price of electricity, arising the need to develop more reliable and efficient electrical energy conversion systems. In this context, emerges the utilization of the modular multilevel converter (MMC) based on submodules. The key to the MMC is modularity, which allows the converter to reach higher performance levels, improving the voltage and current output signals of the converter, in a compact solution. The modularity concept allows the increase of the operation voltage using submodules in series, and the increase of the operating current using submodules in parallel. Additionally, in the event of a submodule malfunction, the converter can be reconfigured and continue the operation, albeit at a lower power level. Due to its versatility, the MMC can be used in a variety of applications, such as HVDC power transmission systems, solid-state transformers, renewable energy interfaces, and more recently, railway power systems. In this context, this paper focuses on the development and experimental validation of a single-phase MMC based on the use of half-bridge submodules applied to a railway static converter, where the main focus lies on the AC side control. The control algorithms are fully described for a single-phase MMC reduced-scale prototype implemented (500 W, 230 V–50 Hz, 200 VDC), connecting two submodules in series in the upper arm, two submodules also in series in the lower arm, the respective driver and command circuits, sensing and signal conditioning circuits, as well as a digital control platform recurring to the DSP TMS320F28379D. Experimental results were obtained to validate each submodule individually, and, later, to verify the operation of the MMC with the set of four submodules.